Disability and employment across Central and Eastern European Countries - Chiara Mussida; Dario Sciulli (IZA Journal of Labor & Development, 2016)
We contribute to the scarce literature focusing on the life outcomes of disabled people in Central and Eastern European Countries by estimating the effects of disability on employment probabilities for six Central and Eastern European Countries. We find that disability negatively affects the employment probabilities of disabled people, especially those with severe disabilities. The effects of disability persist even after controlling for disability benefits, signaling a predominant role for disability per se. The long-term effects of disability are smaller than the short-term effects, suggesting the partial integration of disabled people into the labor market over time, which might favor both social inclusion and a country's economic performance.
Keywords: J14; J15; J21; O15; 330; Disability; Employment probabilities; Caring activities; State dependence; East-Central Europe; Country differences